Fast- and drift-ice communities in the Bothnian Bay and the impact of UVA radiation on the Baltic Sea ice ecology - Piiparinen, Jonna (Helsingin yliopisto, 2011)
The aim of this thesis was to study ecology of Baltic Sea ice from two perspectives. In the first two studies, sea-ice ecology from riverine-influenced fast ice to drift ice in the Bothnian Bay was investigated, whereas the last two studies focus on the sensitivity of sea-ice bacteria and algae to UVA examined in situ. The seasonal sea ice cover is one of the main characteristics of the Baltic Sea, and despite the brackish parental water, the ice structure is similar to polar ice with saline brine inclusions, the sea ice habitat. The decreasing seawater salinity from the northern Baltic Sea to the Bothnian Bay translates to decreasing brine volumes along the gradient, governing the size and community structure of the food webs in ice. However, the drift and fast ice in the Bothnian Bay may differ greatly in this sense, as drift ice may have been formed at more southern locations. Rafting and the formation of snow ice are common processes in the ice field of the Bothnian Bay. As evidenced in this thesis, rafting altered the vertical distribution of organisms and snow-ice formation provided habitable space in the better-illuminated, nitrogen-rich surface layer. The divergence between fast and drift ice became apparent at the more advanced stages, and chlorophyte biomass decreased from fast to drift ice, while the opposite held true for protozoan and metazoan biomass. The brine volumes affected the communities somewhat, and a higher percentage of flagellate species was generally linked to lower brine volumes, whereas chain-forming diatoms were mostly concentrated in layers with larger brine volumes. These results add to knowledge of the ecological significance of the ice cover lasting up to 7 months per year in this area. Sea-ice food webs are generally light-limited, but while increasing light irradiances typically enhance the primary production and further, the secondary production in sea ice, any increase in solar radiation also includes an increase in harmful UVA radiation. The Baltic Sea ice microbial ...